An Epstein-Barr virus transcription unit is at least 84 kilobases long. - Bodescot, M (1986)
We have studied the structure of the Epstein-Barr virus mRNAs expressed in B95-8, a productively-infected Marmoset cell line established from in vitro-infected B-lymphocytes. We constructed a cDNA library from the cytoplasmic polyadenylated RNAs of B95-8 in the lambda gt10 bacteriophage. We present here the analysis of a 3.5 kbp cDNA containing exons transcribed from the US, IR and UL regions of the viral genome. The corresponding transcription unit is at least 84 kbp long. Two exons are transcribed from the US region, five from the IR region and two from the UL region. The exons from the IR region consist of two tandem repeats of a unit containing two exons, 66 and 132 nucleotides, and of a third copy of the 66 nucleotide exon. The exons from the UL region contain an open reading frame coding for a 944 amino acid polypeptide. The C-terminal end of this polypeptide harbors three types of repeated sequences. The corresponding mRNA is the second described of a family of mRNAs produced by alternative splicing of exons transcribed from the US, IR and UL regions.